Renewable Energy Sources Development Risk Analysis and Evaluation: the Case of Azerbaijan - Nuriyev, Mahammad N.; Mammadov, Jeyhun; Mammadov, Joshgun (European Journal of Economics and Business Studies, 2019)
Steady increase in renewable energy production and supply allows gradually substitute environmentally harmful traditional energy systems. Developers of the renewable projects encounter various types of risks, inherent to these projects, and all these risks should be studied in advance and ways of their mitigation developed. In the paper risks related to the development of renewables in Azerbaijan are analyzed and assessed based on experts’ opinion study. Typical for the projects on renewable energy, nine risks and risk components likelihood and their impacts have been evaluated by experts and, based on their opinion, risk levels are calculated, and a risk profile is constructed. In general, risks are sufficiently different. However, energy policy-related, grid access and financial risks are significantly influential and require more attention.
Keywords: renewable energy, risk analysis, risk likelihood, risk impact, risk level